Torpedo maculopathy - Remya Mareen Paulose (Kerala Journal of Ophthalmology, 2017)
Torpedo maculopathy is a rare congenital maculopathy clinically seen as a “torpedo”-shaped lesion temporal to the fovea. We hereby report a 4-year-old female child who on routine evaluation for refractive correction was discovered to have a temporal macular RPE defect with a pointed-oval shape directed toward the foveola. The ophthalmic examination revealed best-corrected visual acuity of 6/12 in both eyes without any changes in biomicroscopy. Her ocular and systemic medical history was unremarkable. Torpedo maculopathy diagnosis was based on the characteristic shape and peculiar location.